A UNIVERSITY-COMMUNITY OUTREACH INITIATIVE: AN INNOVATIVE APPROACH TO SOCIAL WORK PRACTICE EDUCATION - Simpson, Barbara; Sathiparsad, Reshma (Social Work/Maatskaplike Werk, 2011)
Practice education has always been a core component of social work education and provides social work students with opportunities to “learn to practice social work by delivering social work services in agency and community settings” (Bogo, 2006). The purpose of practice education is broadly to enable students to learn to integrate theory and practice, and to develop the knowledge, skills and values necessary for professional practice. One of the issues in transferring such theory into practice is “how to overcome the assumed ‘abstract’ nature of theory in relation to the assumed ‘real’ nature of practice” (Evans, Guile, Harris & Allan, 2010:245), and it is therefore essential to provide students with opportunities to engage in social work processes in the real world. Historically social work agencies acted as the universities’ partners in the practice education of social work students – they provided placement sites and access to social work practice and their supervisors guided and mentored social work students.